Pricing arithmetic Asian put option with early exercise boundary under jump-diffusion process - Laham, Mohamed Faris; Ibrahim, Siti Nur Iqmal; Kilicman, Adem (Institute for Mathematical Research, Universiti Putra Malaysia, 2020)
Arithmetic Asian options is a financial derivatives whose payoff depends on the average of underlying asset which can either be European-style or American-style. The aim of this study is to provide a pricing formulae for arithmetic Asian option with early exercise boundary under jump-diffusion process by implementing probabilistic approach and conditional expected values. We provide numerical examples for approximation formulae of arithmetic Asian option using quadrature methods and compare the results with Monte Carlo simulation which demonstrate the efficiency of the numerical integration technique.